Helicobaceter pylori prevalence in duodenogastrik reflux demostrated by scintigraphic technique in patients with gastric operation - Mehmet CİNDORUK,; Tamer ATASEVER,; Şükrü DUMLU,; Ümit Bilge DOĞAN,; Berna OKUDAN,; Candan TUNÇER,; Mustafa ÜNLÜ,; Uğur KANDİLCİ, (Turkish Journal of Gastroenterology, 2019)
-